Menelaah Konsep Radha’ah sebagai Penentu Mahram dalam Perkawinan - hamdan, Ali (UNIVERSITAS NAHDLATUL ULAMA SUNAN GIRI, 2023)
As a dignified human being and for the sake of protecting offspring/relationships, the implementation of marriage should be carried out in accordance with the rules that have been determined both in Islam and in law. In addition, marriage is a relationship that is recommended by Islam and for those who carry it out it is worth worship in addition to avoiding adultery. however, in the implementation process there are pillars and conditions that must be fulfilled and cannot be abandoned, one of which is the absence of a mahram relationship, whether a mahram due to heredity or because of breastfeeding/radha'ah, so that in this study it leads to the concept of radha'ah as a determination mahram by referring to several opinions, views and perspectives of scholars who explain about radha'ah based on their respective provisions.